ANALISIS PENERAPAN 5S PROSES PRODUKSI PADA UKM KERUPUK LATANSA - Wulandari Ramadhani, Ringgie; Sirait, Ganda (Computer Science and Industrial Engineering, 2025)
UKM Kerupuk Latansa in Batam faces various challenges in its production process, including disorganized tool and material placement, a suboptimal working environment, and inefficient production time. These issues potentially lower productivity and product quality. This study applies the 5S method (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke) to improve production efficiency and workplace organization. A quantitative approach was used, collecting data through direct observations, interviews, and work time measurements. The results show that after implementing 5S, the average cycle time decreased from 15.37 seconds to 13.82 seconds, and production output increased from 2,250 to 2,500 packs per month. In the Seiri stage, unnecessary items were removed from the workspace to create a cleaner and more comfortable working environment. Seiton was implemented by organizing production tools, such as impulse sealers, for easier access. Seiso involved routine cleaning of the workspace and equipment to prevent packaging defects. Seiketsu ensured standardized procedures for workplace cleanliness and organization. Finally, Shitsuke established a culture of discipline in maintaining cleanliness and order, with regular evaluations to sustain the 5S implementation. With a cleaner and more organized environment, employee comfort and productivity significantly improved.